Run-time mapping for dynamic reconfiguration management in embedded systems. (14th March 2011) - Benoit, Pascal; Torres, Lionel; Sassatelli, Gilles; Robert, Michel; , Nicolas Saint-Jean
Dynamic reconfiguration provides attractive features such as hardware flexibility and adaptability. Unfortunately, the lack of programming tools to manage it has limited its use in current SoC. This paper presents a method to abstract dynamic reconfiguration management at design time. Dynamic hardware multiplexing is a generic principle based on a scheduler dedicated to the management of reconfigurable resources at run-time. Formal background, implementation, simulation results and validations are exposed to illustrate the contribution of this study.